2020
DOI: 10.3351/ppp.2020.4298645632
|View full text |Cite
|
Sign up to set email alerts
|

Inequality Restructured: A Regional Comparison of the Occupational Position of Young People Before and After the Great Recession of 2008

Abstract: A bstract Developments in the youth labour market are regularly framed as successful by the UK Government who argue that young people have a growing and vibrant jobs market. Sociological discourse has tended to focus on the growth in precarious work and the substantial decrease in the availability of employment for young people. Far less attention has been paid to the parallel issue of whether these changes are associated with shifts in occupational level. Yet occupational position remains one of the most powe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 27 publications
0
1
0
Order By: Relevance
“…They also found that young people were struggling to gain entry to the labour market, and after obtaining work their ability to acquire better pay and conditions was hampered by a lack of opportunities. This is buttressed by Ralston and Formby (2020) who found that the youth labour market outside of the South-East collapsed in 2010 and has since seen few signs of significant recovery. Overall, the overriding theme in relation to the labour market has been a restructuring of work which has seen an increase in precarity, particularly for young workers (Gregg and Gardiner, 2015;Hardgrove et al, 2015;Beatty et al, 2017;Formby, 2017;Hoskins et al, 2018).…”
Section: Global Financial Crisis -2007 To 2018mentioning
confidence: 99%
“…They also found that young people were struggling to gain entry to the labour market, and after obtaining work their ability to acquire better pay and conditions was hampered by a lack of opportunities. This is buttressed by Ralston and Formby (2020) who found that the youth labour market outside of the South-East collapsed in 2010 and has since seen few signs of significant recovery. Overall, the overriding theme in relation to the labour market has been a restructuring of work which has seen an increase in precarity, particularly for young workers (Gregg and Gardiner, 2015;Hardgrove et al, 2015;Beatty et al, 2017;Formby, 2017;Hoskins et al, 2018).…”
Section: Global Financial Crisis -2007 To 2018mentioning
confidence: 99%